The Introduction to Self-Reflection through Sociolinguistics - Zainal Shah, Norshima; Saayah Ismail, Amnah; Samad, Norlela (International Journal of Engineering and Technology, 2018)
Reflection is a powerful thinking tool. This action research aims to introduce reflective thinking to 32 students undertaking the Sociolinguistics course. The students were introduced to seven selected teaching activities such as using short stories, writing  journal article review, writing a report after an interview and producing a video, to name a few during the course. At the same time, the students were exposed to a series of reflective thinking activity following the Model of Holistic Reflection. They consistently wrote about their reflections and answered a questionnaire on their learning experience. The planned activities gave the students a chance to put sociolinguistics theory into practice and was most apparent in the activity of interviewing a friend of another ethnicity and producing a short video where both activities were rated as the most liked and enjoyable activity in the course. The students proposed several interesting alternatives to make lessons better according to their preferences. Overall, through reflective thinking, the students demonstrated their ability to transform what they have learned into everyday practice. Additionally, the lecturer also benefited from students’ feedback in planning and improving the course. More invaluable data can be obtained in utilising the methodology used in this study to teach other courses in the future.
Keywords: Learning Experience; Reflection; Reflective Thinking; Sociolinguistics; the Holistic Reflection Model